"The End of Childhood": The international tours of the Teatro Municipal General San Martín during the last military dictatorship in Argentina (Quinto Sol, 2024)
This study reconstructs and analyzes the development of the two international tours carried out by the Teatro Municipal General San Martín (Buenos Aires, Argentina), under the direction of Kive Staiff, in the context of the last military dictatorship (1976-1983): the so-called "Spanish-American Tour", between April and June 1980, and the visit to the Union of Soviet Socialist Republics (USSR), in 1982. The study of these experiences will show how the management implemented by the theater director was crossed by negotiations and transactions between the cultural field and the various interests projected by the military regime at the international level. We argue that, on the one hand, these initiatives contributed to the consolidation of Staiff's management project by making Argentine theater visible beyond national borders. On the other hand, we identify the instrumentalization of these cultural proposals in the realization of the political objectives pursued by the dictatorship.
Keywords: theatre management; dictatorship; international politics; cultural management